Wounded Healers: A Multistate Study of Licensed Social Workers' Behavioral Health Problems. Issue 2 (7th February 2018) - Straussner, Shulamith Lala Ashenberg; Senreich, Evan; Steen, Jeffrey T
Abstract: Studies indicate that helping professionals are disproportionately affected by behavioral health problems. Among social workers, the nature and scope of these problems are understudied. This article reports the findings of a 2015 survey of 6, 112 licensed social workers in 13 states regarding their problems with mental health; alcohol, tobacco, and other drugs; and gambling. To ascertain whether these problems preceded or developed during their social work careers, the periods of time when these issues were experienced were identified. Results indicate that 40.2 percent of respondents reported mental health problems before becoming social workers, increasing to 51.8 percent during their social work career, with 28 percent currently experiencing such problems. Nearly 10 percent of the sample experienced substance use problems before becoming social workers, decreasing to 7.7 percent during their career. Analyses by race or ethnicity, sex, and age identified between-group differences in the prevalence of these problems. The article concludes with a discussion of the implications for the social work profession.